2016
DOI: 10.1155/2016/7058537
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Botulinum Toxin Type A for the Treatment of Excessive Secretion after Submandibular Gland Transplantation in Rabbits

Abstract: Objectives. To investigate whether botulinum toxin type A (BTXA) could control excessive secretion after submandibular gland (SMG) transplantation in rabbits and its possible mechanisms. Methods. A new SMG transplantation model was established in rabbit. 30 successfully constructed models were randomly assigned to five groups including control group and four experimental groups. Secretion outputs were used to analyze the effect of BTXA injection on excessive secretion. Hematoxylin and eosin (HE) staining, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The absence of acetylcholine in synapses causes functional chemical denervation, preventing salivary secretion . BoNT‐A also showed water transport system interference in glandular cells by decreasing the availability of aquaporin‐5 channels in submandibular rabbit glands …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of acetylcholine in synapses causes functional chemical denervation, preventing salivary secretion . BoNT‐A also showed water transport system interference in glandular cells by decreasing the availability of aquaporin‐5 channels in submandibular rabbit glands …”
Section: Introductionmentioning
confidence: 99%
“…6 BoNT-A also showed water transport system interference in glandular cells by decreasing the availability of aquaporin-5 channels in submandibular rabbit glands. 7 Decrease in glandular volume, acinar, and ductal cell counts have been reported as among morphological effects after intraglandular application of BoNT-A. 8 Studies regarding the treatment effects with repeated applications of BoNT-A in salivary glands are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, botulinum neurotoxin A (BTXA) inhibits acetylcholine release by binding to an acceptor protein on the presynaptic membrane of the acetylcholine nerve terminal. 32 It has been reported that BTXA was effective in reducing the secretion of the transplanted SMG in patients 33 and rabbits, 34 , 35 which provided additional evidences for the functional reinnervation of the cholinergic nerves in transplanted SMG.…”
Section: Discussionmentioning
confidence: 93%
“…Clinically, botulinum toxin A (neurotoxic protein) has been utilized to manage the increase in the salivary gland secretion, but the exact mechanism of this agent on this gland regarding its function and histology remains unclear (1). In fact, clostridium botulinum bacteria are the source of Botulinum toxin A which was used also in cases of excessive lacrimation, drooling, and hyperhidrosis (2,3). The action of Botulinum toxin A is depending on the inhibitory effect on acetylcholine release at the presynaptic region, as it acts on the parasympathetic nerve terminals (cholinergic nerve terminals) which lead to localized chemical block with neuronal activity loss in the target tissue (4).…”
Section: Introductionmentioning
confidence: 99%